Determination of Cultural Tourism Development Strategy in the Special Capital Region of Jakarta Using the Dynamic Model Method - Prawesti, Gita; Supriatna, Ade; Isniah, Sarah; Khoirunisa, Alfiah (Spektrum Industri, 2025)
DKI Jakarta has great potential for tourism development, but it has some shortcomings, especially in cultural tourism, particularly museums. The potential for tourism development can be further enhanced with the increasing number of tourists. The increase in the number of tourists can have both positive and negative impacts. The positive impacts include increased regional income, GRDP, MSME income, and employment. The negative impacts include cultural filtration, environmental pollution, the risk of disease transmission, and so on. To bridge these issues, this research was conducted to obtain optimal strategies for the cultural tourism sector in DKI Jakarta to increase MSME income and Gross Regional Domestic Product (GRDP) of DKI Jakarta. This research develops a dynamic model to determine optimal strategy scenarios by considering MSME income and GRDP of DKI Jakarta using Powersim. Policy scenarios for the development strategy of cultural tourism in DKI Jakarta are formulated based on a combination of schemes determined from the variables created. These variables consist of GRDP, MSME income, and other supporting tourism sectors. The selection of the optimal strategy for the sustainable cultural tourism sector can be determined with scenarios of increasing and decreasing parameter values. The chosen scenario is a combination of parameter values based on the results obtained. The scenario of increasing parameter values can be chosen for MSME income and GRDP factors in DKI Jakarta, as it results in an increase of 5% and 0.008%, respectively.